STRATEGI KOLABORASI ORANGTUA DENGAN KONSELOR DALAM MENGEMBANGKAN SUKSES STUDI SISWA - Nugraha, Ariadi; Rahman, Fuad Aminur (JURNAL KONSELING GUSJIGANG, 2017)
Family is an important factor in the development of self-confidence, academic and student life success. Some literature has shown that family background, including socioeconomic status, parental involvement, and expectations of parents, influenced the development of students' learning and career development (Weiser and Riggio, 2010). Therefore, based on the above school counselors need to consider to improve interaction and collaboration with parents and trying to develop a positive perception of the students in terms of the students' success. Collaboration is an activity where there is cooperation between the various parties in realizing the goal of education, both parties from both inside and outside the institution. Collaboration in guidance and counseling is the cooperation activities between BK teacher / counselor with a number of parties in order to achieve the purpose of guidance and counseling programs, therefore, need their good collaboration strategy between counselor and parents, especially in terms of developing successful students study